Pengaruh Konsentrasi Pupuk Organik Cair Dan Takaran Pupuk Kandang Sapi Terhadap Pertumbuhan Dan Hasil Tanaman Selada (Lactuca sativa L.) Varietas Grand Rapids - Hanipah Hanipah; Nurdin Hadirocmat; Odang Hidayat (OrchidAgro, 2021)
The aim of this experiment was to study the effect of concentration liquid organic fertilizer and doses cow manure on the growth and yield of grand rapids variety of lettuce, carried out in the practice of Tanjungsari Sumedang SMK PPN, located at an altitude of 850 meters above sea level. The experiment starts from June 2018 to August 2018. The experimental design used was a Randomized Design facto pattern group consisting of two factors and repeated three times. The first factor is liquid organic fertilizer nasa (p) with 5 levels: p1 = 0 ml / liter of water, p2 = 1 ml / liter of water, p3 = 2 ml / liter of water, p4 = 3 ml / liter of water, p4 = 4 ml / liter of water. The second factor is cow manure (k) consisting of 4 levels, namely: k1 = 0 ton / ha, k2 = 5 ton / ha, k3 = 10 ton / ha, k4 = 15 ton / ha. The results of the experiment show: There was no interaction between liquid organic fertilizer    and cowshed fertilizer on observations of plant height, number of leaves, weight per plant, weight per sample, weight per plot and root volume in lettuce. The treatment of liquid organic fertilizer at concentrations of p3 (3,0 ml/liter of water) showed the best results on plant height, number of leaves, and yield of weight per plot and significantly different from observations of weight per plant and root volume. Cow manure showed no significant effect on all plant height, number of leaves, weight per plant, weight per sample, weight per plot and root volume in lettuce.